Arterial compression by an adjacent venous stent graft in a patient undergoing dialysis. Issue 6 (November 2020) - Chen, Tsung-Yan; Wu, Chih-Cheng; Hsieh, Mu-Yang
Background: Stent graft is effective for management of balloon-angioplasty-related complications in hemodialysis access. These complications include post-angioplasty venous rupture, dissection/recoil, and acute formation of pseudoaneurysm. Case report: We report a stent-graft complication that caused immediate acute arterial insufficiency by external compression. An 84-year-old woman presented with acute arteriovenous graft thrombosis. During percutaneous balloon thrombectomy, a stent graft was placed because of persistent recoil and mural thrombus, but the flow into the arteriovenous graft immediately ceased. External compression of the brachial artery was observed. A nitinol self-expandable stent was deployed in the brachial artery to oppose the external compression. The flow in the arteriovenous graft was recovered. Conclusion: This case demonstrates the possibility of arterial compression by an adjacent venous stent graft, especially in a patient with a thin habitus and a brachial–brachial arteriovenous graft. Detailed identification of the outflow vein anatomy before stent implantation is mandatory to avoid such a complication.